Store Advertising Strategy In Tuban In Increasing Product Appeal - Rohid, Nibrosu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Advertising strategy of Ceker Gobyozz Byozz Tuban Shop and its impact on business growth. Using the Diffusion of Innovation Theory by Everett M. Rogers, this study identifies how innovation in products and advertising strategies can be applied to small businesses. This shop utilizes the trend of spicy food that is popular among young people as the main innovation, accompanied by promotions through social media such as Instagram, Facebook, and WhatsApp, as well as print media in the local community. This strategy is implemented in stages, starting from word-of-mouth (WOM) promotion to the use of more modern media. The results of the study show that a well-integrated advertising strategy can significantly increase the number of visitors. This shop is able to attract around 50-70 visitors per branch per day, with a total turnover of 120 million rupiah per month. In addition, involvement in the local community accelerates the diffusion of innovation and helps the shop reach a wider market. Consumer adoption decisions are influenced by product quality and positive experiences at the shop, which creates customer loyalty. In conclusion, an innovative and targeted advertising strategy is the key to the success of Ceker Gobyozz Byozz Shop, providing important insights for small businesses in developing their businesses through effective promotions.